BME402 – Microbial Genomic (Genomik Mikrob) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK
Second Semester Examination 2022/2023 Academic Session July/August 2023 BME402 – Microbial Genomic (Genomik Mikrob) Duration: 2 hours (Masa: 2 jam)